Satellite Module Reference Design - Mr.S.Arunprathap, Mr.T.P.Balakrishnan, Mr.M.Dinesh Kumar, Mr.M.Vijayan, Mr.M.Yougan (International Journal of Modern Agriculture, 2021)
The Satellite Module Reference Design consists of Bluetooth Low Energy with CAN design which can be intended for Bluetooth passive entry passive start (PEPS) and phone as a key, digital key access system. The design demonstrates that how the control area network flexible data rate (CAN-FD) communication capabilities can be implemented with our Bluetooth wireless MCUs for the systems that require higher bandwidth in-vehicle network communications. The higher network bandwidth allows for the raw measurement data, such as angle of arrival IQ data, which can be directly sent to the central car access module for processing. A unique feature which can be implemented in the TIDA-020032 design is the ability to auto-address. Auto-addressing allows all satellite modules to be flashed with the same firmware instead of requiring each module to be flashed with a different CAN ID and thus manufacturing becomes easier. The benefits includes that during the sleep state the power consumption is reduced, and for the improved manufacturing the CAN auto-addressing method can be used, connection monitor capabilities for the better and improved Bluetooth localization accuracy. The compact printed-circuit board (PCB) can be used to measure the Bluetooth angle of arrival (AoA) and the received signal strength index (RSSI).